2017
DOI: 10.3171/2017.3.spine161169
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of hybrid stabilization on the risk of proximal adjacent-segment degeneration following lumbar spinal fusion using an interspinous device or a pedicle screw–based dynamic fixator

Abstract: OBJECTIVEPedicle screw-rod–based hybrid stabilization (PH) and interspinous device–based hybrid stabilization (IH) have been proposed to prevent adjacent-segment degeneration (ASD) and their effectiveness has been reported. However, a comparative study based on sound biomechanical proof has not yet been reported. The aim of this study was to compare the biomechanical effects of IH and PH on the transition and adjacent segments. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…In general, the greater the strength of internal fixation, the more likely the adjacent segments are unstable and degenerate [13]. After adopting CAPSI in osteoporotic vertebral body, the fixation effect is obviously better than CPS, and the activity of the surgical segment become smaller, which leads to the compensatory increase of the upper and lower vertebral body movement range of the surgical segments, and results in increased stress on adjacent segmental intervertebral discs as well as facet joints followed by the accelerating degeneration of adjacent segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the greater the strength of internal fixation, the more likely the adjacent segments are unstable and degenerate [13]. After adopting CAPSI in osteoporotic vertebral body, the fixation effect is obviously better than CPS, and the activity of the surgical segment become smaller, which leads to the compensatory increase of the upper and lower vertebral body movement range of the surgical segments, and results in increased stress on adjacent segmental intervertebral discs as well as facet joints followed by the accelerating degeneration of adjacent segments.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the cause of ASD remains unclear. Some scholars believe that internal fixation will accelerate the degeneration of adjacent segments, which is an independent risk factor for ASD [13], while some studies believe that the occurrence of ASD is mainly related to the age of patients and the type of surgery they undergo. There are many factors related to the degeneration of the intervertebral disc in the anterior adjacent segment, and internal fixation is not the main cause of ASD [14].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Dynamic stabilization techniques do not appear be clearly protective against adjacent segment disease, although biomechanical models suggest that they may do so. 33,39,40 A review by Wang and colleagues pooled studies to assess the risk of lumbar adjacent segment disease in spinal fusion to compare to disc arthroplasty and concluded that fusion carried a higher risk of adjacent segment disease. 41 Definitive data on other types of motion preservation devices is lacking.…”
Section: Adjacent Segment Diseasementioning
confidence: 99%
“…Pedicle screw fixation in lumbar intervertebral fusion procedures is considered to be the current gold standard treatment. By providing increased rigidity in all three main motion directions, the transpedicular stabilisation allows wide decompression in severe lumbar degenerative diseases with moderate to excellent clinical success [2,3]. However, pedicle screw instrumentation comes at the cost of high invasiveness.…”
Section: Introductionmentioning
confidence: 99%